Estimating Usual Intakes Affecting the Macronutrient and Micronutrient Distribution among the Adolescent Population: A Study of Slovenian National Dietary Surveys SI.Menu 2017/18 - Hristo Hristov; Rok Poličnik; Matej Gregorič; Masa Hribar; Igor Pravst (Proceedings)
Estimating the dietary intakes of certain populations is essential for making the right decisions on a national level in respect to nutrition, epidemiology, economic, environmental, and policy applications. The objective of this study is to determine the usual dietary intakes of macronutrients and micronutrients, considering how the population are individually affected by food and nutrient intakes. From the Central Register of Population, employing a two-stage stratified sampling procedure, a representative sample of adolescent participants was randomly selected, according to sex and place of residency. Two non-consecutive 24 h dietary recalls were collected using a web-based Open Platform for Clinical Nutrition (OPEN) software. Additionally, a food propensity questionnaire was used to collect information about a participant’s frequency of food consumption. A total of 468 adolescent were included in the analyses: 10–12 years old (N = 194), 13–14 years old (N = 93), and 15–17 years old (N = 181). The analyses reveal dietary patterns that were different both between age groups and between genders. An overall lower variability in energy and fat intakes but a much higher variability for micronutrients was observed. Unbalanced usual dietary intakes were especially represented through high consumptions of foods that are high in sugar as well as fresh and processed meats, and low intakes of legumes and legume products, fruits and vegetables, while a higher variability was detected within dairy products. Determining the usual dietary intake using the Multiple Source Method provided wider intake distributions that allowed for more precise estimates for the prevalence of inadequate/excessive intakes for analyzed subpopulations. The overall results suggest a deviation from national dietary guidelines and a call for public health interventions in order to improve dietary patterns.